METODE SUGESTOPEDIA UNTUK MENINGKATKAN KETERAMPILAN MENULIS PUISI SISWA KELAS VIII SMPN 6 SUNGAI RAYA - Syarmila, Syarmila; Wartiningsih, Agus; Muzammil, Ahmad Rabi’ul (Universitas Tanjungpura, 2023)
The purpose of this study was to describe the application of the Suggestopedia learning method to improve the poetry writing skills of grade 8 students of SMP Negeri 6 Sungai Raya in the 2022/2023 academic year. The research findings are based on a teacher using the Teacher Performance Assessment Tool (IPKG) and his observations of students in two learning cycles. Based on learning practice it is proven that this method can increase the value of students' poetry writing skills, with an average score of 67.62 for the first rubric of cycle I compared to the previous rubric. The previous cycle corresponded to an average value of 62. Final Results The average value of cycle II reached 74.56 above the average value of cycle I. However, in cycle II the average value was 79.82 compared to the value of cycle 1 and increased by 16 .63 compared to pre-cycle values. The percentage of completeness in cycle II has also reached an indicator of success in class learning, namely 75% of the total number of students in the class.